KEANEKARAGAMAN JENIS DAN PEMANFAATAN TUMBUHAN OBAT DI KELURAHAN BATU PUTIH BAWAH KOTA BITUNG - Ekasari Matatula; Euis F. S. Pangemanan; Marthen Th. Lasut (Universitas Sam Ratulangi, 2022)
ABSTRACT This study aims to determine the diversity of species and the use of plants as traditional medicine by the people of Batu Putih Bawah Village, Bitung City. This research was conducted in August 2020 in the Batu Putih Bawah village, Bitung City. The method used in this research is interviews and field observations. The informant selection technique used is purposive sampling technique, respondents are selected based on those who have knowledge of medicinal plants and their use. Based on the research results, it is known that there are 56 types of plants from 40 families that are used as traditional medicine. The most common member of the family is Euphorbiaceae (4 species). Trees are the most used habitus (18 species), and the leaves are the most widely used for processing into medicine. Sources of plant acquisition are generally found in the yard of 46% (26 species), the method of processing by boiling is mostly done by 46% (28 species) and the benefits of medicinal plants can heal the liver, asthma, reduce high fever, diarrhea, malaria, sarampa, wounds. burns, ulcers, stomach acid, broken bones and so forth. Keywords: Species diversity, utilization of medicinal plants, Batu Putih Bawah Village